Pengaruh Leverage, Kepemilikan Manajerial dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Kesehatan Yang Terdaftar Di BEI Periode 2021-2023 - Wayan Septiani Jayati, Ni; Angelica Cindiyasari, Shiwi (Journal of Accounting and Finance Management, 2024)
This research aims to analyze the influence of leverage, managerial ownership and profitability on company value in health sector companies listed on the Indonesia Stock Exchange (BEI) for the 2021-2023 period. This research sample consisted of 30 companies selected through a purposive sampling method. Testing was carried out using the data panel regression analysis with EViews 12 software to analyze the influence of the independent variable on the dependent variable. The research results show that profitability has a positive and significant influence on company value, while leverage and managerial ownership do not have a significant effect on company value. Based on the results of the F test, leverage, managerial ownership and profitability simultaneously have a significant effect on the value of health sector companies. In addition, the coefficient of determination test results of 86.39% show that the independent variable is able to explain 86.39% of the dependent variable, with the remaining 13.61% explained by other variables.